English Vocabulary Teaching Based on Psycholinguistics and Brain Science - Zheng, Min (Journal of Educational Research and Policies, 2026)
This paper explores a new theoretical framework for college English vocabulary teaching from the perspectives of psycholinguistics and brain science. It first introduces cognitive linguistics theories, such as prototype category theory, conceptual metaphor theory, and schema theory, which provide important guidance for vocabulary teaching and emphasize the importance of understanding and memorizing vocabulary through cognitive processes like analogy and induction. Subsequently, the paper discusses findings from mental lexicon research, highlighting the necessity of deepening vocabulary learning in context and the importance of establishing semantic networks through association and reorganization. Furthermore, the paper applies insights from memory psychology, examining the roles of different types of memory and their impact on language learning. It further analyzes the pattern recognition mechanisms the brain relies on when processing linguistic information, as well as the influence of neural activity mechanisms on vocabulary memory capacity. Research indicates that the brain achieves deep understanding and memory of vocabulary through the coordinated work of specific brain regions. The activation of brain regions involved in semantic memory, working memory, and semantic association is closely related to human language ability. Finally, the paper emphasizes that in the era of artificial intelligence, education needs to pay more attention to the implications of brain science, understanding the cognitive forms of brain memory and the neural mechanisms of language memory. This will not only enhance teaching efficiency but also stimulate students’ interest in learning, promoting deeper understanding and long-term memory in language acquisition. By integrating cognitive linguistics theories with brain science research, teachers can design more effective teaching strategies, thereby improving the efficiency and effectiveness of students’ vocabulary learning.